2014
DOI: 10.1002/anie.201407807
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible and Selective Inhibitor of Monoacylglycerol Lipase Ameliorates Multiple Sclerosis

Gloria Hernández‐Torres,
Mariateresa Cipriano,
Erika Hedén
et al.

Abstract: Monoacylglycerol lipase (MAGL) is the enzyme responsible for the inactivation of the endocannabinoid 2-arachidonoylglycerol (2-AG). MAGL inhibitors show analgesic and tissue-protecting effects in several disease models. However, the few efficient and selective MAGL inhibitors described to date block the enzyme irreversibly, and this can lead to pharmacological tolerance. Hence, additional classes of MAGL inhibitors are needed to validate this enzyme as a therapeutic target. Here we report a potent, selective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…2013) and 1,3,4-oxadizol-3-ones (Käsnänen et al 2013) had shown MGL-inhibitor activity, but these classes generally showed also inhibition of other serine hydrolases like FAAH. Recently, a compound lacking reactive functionalities, CL6a (Tuccinardi et al 2014, Figure 4) has been described as a micromolar reversible inhibitor of MGL, addressing the catalytic pocket, similarly to what had been observed for the crystal structure with the non-covalent inhibitor ZYH (Figure 2), and a lipophilic ester (Hernandez-Torrs et al, 2014, Comp21 in Figure 4) has been shown to inhibit MGL with sub-micromolar potency.…”
Section: Mgl Inhibitorssupporting
confidence: 52%
“…2013) and 1,3,4-oxadizol-3-ones (Käsnänen et al 2013) had shown MGL-inhibitor activity, but these classes generally showed also inhibition of other serine hydrolases like FAAH. Recently, a compound lacking reactive functionalities, CL6a (Tuccinardi et al 2014, Figure 4) has been described as a micromolar reversible inhibitor of MGL, addressing the catalytic pocket, similarly to what had been observed for the crystal structure with the non-covalent inhibitor ZYH (Figure 2), and a lipophilic ester (Hernandez-Torrs et al, 2014, Comp21 in Figure 4) has been shown to inhibit MGL with sub-micromolar potency.…”
Section: Mgl Inhibitorssupporting
confidence: 52%
“…In addition, 2-AG treatment also increased axonal ramification and, as observed for axonal elongation, this increase was prevented when neurons were pre-incubated for 1 h with the CB1R antagonists (Figure 1F). Moreover, we tested the effect of increasing endogenous levels of 2-AG by using UCM-03025, a monoacylglycerol lipase (MAGL) inhibitor that prevents 2-AG degradation (Hernández-Torres et al, 2014). Similar to what occurred when neurons were treated with 2-AG, MAGL inhibition also promoted axonal elongation (467.54 ± 25.35 μm for UCM 1 μM vs. 324.15 ± 14.42 μm in control neurons, Kruskal-Wallis, Dunn’s multiple comparisons test, p < 0.0001, Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…UCM-03025 was a gift from María Luz Lopez Rodriguez laboratory (Complutense University, Madrid; Hernández-Torres et al, 2014). CB1R interference RNA and scrambled RNA plasmids (Origene) were a kind gift of Dr. Ismael Galve-Ropert (Universidad Complutense, Madrid) and were previously validated (Diaz-Alonso et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Also, oligodendrocyte (the cell responsible for the production of myelin) excitotoxicity and white matter damage have been reported to be ameliorated by the administration of a MAG lipase inhibitor via enhancing endogenous levels of 2-AG, in contrast to the inhibition of FAAH, which had no effect in this animal model of MS (Bernal-Chico et al 2015). In another study, EAE was also ameliorated via the selective inhibition of MAG lipase (Hernández- Torres et al 2014).…”
Section: Experimental Evidencementioning
confidence: 92%